Evaluation of the Implementation of the Independent Curriculum Using the CIPP Model (Context, Input, Process and Product) - Mahfud Heru Fatoni; Muhammad Alfan Bahij; Baron Santoso; Yekti Handayani (Jurnal Pedagogi dan Inovasi Pendidikan, 2026)
This study aims to evaluate the implementation of the Independent Curriculum at MITQ Al Manar Klaten using the CIPP (Context, Input, Process, and Product) evaluation model. This research is an evaluative study with a qualitative approach. Data were collected through in-depth interviews, participatory observation, and documentation studies, with informants such as the madrasah principal, vice-principal, and teachers. Data analysis used the Miles, Huberman, and Saldana model, which includes data condensation, data presentation, and conclusion drawing. The results show that in terms of context, the madrasah environment supports the implementation of the Independent Curriculum and some teachers have gained sufficient understanding through the training they have attended. In terms of input, the madrasah has prepared qualified human resources, provided both online and offline training, and equipped learning facilities and infrastructure. In terms of process, teachers have implemented learning according to the stages of the Independent Curriculum, from planning, implementation, to evaluation, although obstacles such as suboptimal student participation have been encountered. In terms of product aspects, learning outcomes and reinforcement of the Pancasila Student Profile have not yet fully demonstrated optimal results because the curriculum's implementation is still relatively new and requires time to demonstrate significant impact. Therefore, ongoing evaluation and strengthening strategies are needed to increase the effectiveness of the Independent Curriculum implementation in schools.